ON HEAVY PENALTY FOR INTERNATIONAL HOMICIDE (International relations and international law Journal, 2020)
The crime of intentional homicide in criminal law of various countries is the first mission. Domestic scholars focus attention on the crime of intentional homicide at normative level and legal philosophy level. Author conducts inspection of intentional homicide from four aspects: аt the normative level, expands the crime ladder of Beccaria, and explains the function of criminal law sentenced to felony for committing homicide; аt the crime level, explains the necessity of killing penalties from anthropological and sociological level; аt the philosophical level, discusses the philosophical presupposition of punishing on homicide from moral and legal responsibility; аt the political level, discusses the inevitability of homicide in elements of nature before the modern society. The author i explains in the article the purpose of criminal law on human right’s protection. The legal protection of the right to life is bound to be a category of moral rationality. Therefore, the protection of the victim’s right of life should belong to the category of criminal law.Key words: intentional homicide, crime, responsibility, protection of victims, national fines.